Human rights in Africa : from the OAU to the African Union - Murray, Rachel (Rachel H.) (Cambridge University Press, 2004)
This work examines the role of the Organization of African Unity, now the African Union, and how it has dealt with human rights since its inception in 1963. It considers the role of its main institutions both under the OAU and its transformation recently into the African Union.